This preview shows page 1. Sign up to view the full content.
Unformatted text preview: gin, we expand f (tn 1 +
cih Yi) using (3.1.6) to obtain
f (tn 1 + cih Yi) = f + ft cih + fy (Yi ; y(tn 1)) + 1 ftt (cih)2 + 2fty (cih)(Yi ; y(tn 1))+
; ; ; ; fyy (Yi ; y(tn 1))2] + O(h3):
; All arguments of f and its derivatives are at (tn 1 y(tn 1)). They have been suppressed
Substituting the exact ODE solution and the above expression into (3.2.3a) yields
; y(tn) = y(tn 1) + h
i=1 ; bi f + ft cih + fy (Yi ; y(tn 1)) + O(h2)]:
; The expansion of Yi ; y(tn 1 ) will, fortunately, only require the leading term thus, using
Yi ; y(tn 1) = h aij f + O(h2):
; ; j =1 Hence, we have y(tn) = y(tn 1) + h
i=1 bi f + ft cih + hffy s
j =1 aij + O(h2)]: Equating terms of this series with the Taylor's series (3.1.8) of the exact solution yields
(3.2.5c) with l = 1, (3.2.5c) with l = 2, and (3.2.7) with k = 2. We have demonstrated
the equivalence of these conditions when (3.2.5b) is satis ed.
Remark 1. The results of Theorem 3.2.1 and conditions (3.2.5) and (3.2.7) apply to
both explicit and implicit methods.
Let us conclude thi...
View Full Document
This document was uploaded on 03/16/2014 for the course CSCI 6820 at Rensselaer Polytechnic Institute.
- Spring '14